RESEARCH COMPETENCE COMPONENT STRUCTURE OF ACADEMIC AND SCIENTIFIC STAFF - Olga Yaroshenko (Неперервна професійна освіта: теорія та практика)
The article reveals the role of research competence in the career growth of academic staff, outlines the functions of research competence in the context of national science entry into the European Research Area. The research competence of an academic is considered in terms of the condition and result of academic’s professional activity. On the basis of literary sources analysis and taking into account the mission of the universities’ scientific activity, the concept of an academic’s research competence as a personal quality, being developed on the basis of a combination of knowledge, skills, values, has been formulated. Cognitive, research and value components have been distinguished in the structure of an academic’s research competence. The cognitive component is: knowledge of research methodology, types and methods and means of research, as well as knowledge of the research area. The activity component is the ability to analyze and evaluate scientific materials, to use knowledge that collectively constitutes the cognitive component, in one’s own research activities and in the education of higher education students through research; the ability to conduct a scientific experiment, to process and present scientific results. The value component is characterized by an awareness of the personal importance of scientific activity, its role in professional activity; ethical relationships shown in research with other researchers, academic integrity and tolerance. The author has expressed the opinion that it is inappropriate to consider motivation for research activity as a separate component of research competence. The argument is that motivation is an incentive to act, not an awareness of something specific, so it should be considered in the structure of readiness for activity. The characteristics of each component of an academic’s research competence have been presented.